2‐Aryl‐2, 4‐dihydro‐5H‐[1, 2, 3]triazolo[4, 5‐d]pyrimidin‐5‐ones as a New Platform for the Design and Synthesis of Biosensors and Chemosensors. Issue 3 (9th January 2020) - Eltyshev, Alexander K.; Minin, Artem S.; Smoliuk, Leonid T.; Benassi, Enrico; Belskaya, Nataliya P.
Abstract : 2‐Aryl‐2, 4‐dihydro‐5 H ‐[1, 2, 3]triazolo[4, 5‐ d ]pyrimidin‐5‐ones (DTPs), which may be considered as analogues of 8‐azapurines, were synthesised. Their structural aspects in the ground and excited states, electronic distributions, and non‐covalent intramolecular interactions were studied using time‐dependent density functional theory. Photophysical investigations demonstrated the variability of the absorption and emission parameters of the DTPs depending on their structure, microenvironment, and external stimuli. The aggregation‐induced emission enhancement effect was confirmed by studying the emission of DTPs in the solid state and by spectral titrations in H2 O‐dimethyl sulfoxide (DMSO) and EtOH‐DMSO mixtures. Further investigation revealed the selective sensitivity of DTPs to acids, which strongly depended on their structure. Reversible interactions were found between the DTPs and HCl and subsequently triethylamine, both as vapour stimuli and in solution. Cell imaging experiments showed the potential of the DTPs in fluorescence microscopy bioimaging applications. These findings show that DTPs can be used to fabricate bio‐ and chemosensors. Abstract : A new class of blue and blue‐green fluorophores based on 1, 2, 3‐triazolopyrimidines (DTPs) with tunable photophysical properties was designed and synthesised. DTPs exhibited multifunctional properties, aggregation‐induced emission enhancement, selective sensing of solvents with different polarities, sensing of acid in solution and vapour, and potential applicability in fluorescence microscopy bioimaging.